Traditional Guesthouse Architecture and Sustainable Tourist Engagement: A Qualitative Study of Tunisian Guesthouses - MAGHRAOUI , Souad; NAJAR , Manel (Revue Internationale des Sciences de Gestion, 2025)
This research examines how traditional guesthouses can enhance tourists’ experiences while promoting sustainable engagement. Based on semi-structured interviews with 20 domestic and international visitors, our findings show that tourists seek authenticity, cultural immersion, and emotional connection while balancing comfort, modernity, and tradition. Traditional architectural elements—such as handcrafted materials, spatial organization, and aesthetic details—strongly influence accommodation choice, fostering emotional attachment, satisfaction, and loyalty. Visitors also report adopting sustainable behaviors when encouraged through clear guidance, including energy and water conservation, recycling, and support for local products. Participants emphasize the importance of comfort improvements, interactive sustainability-focused communication, and offerings involving local stakeholders, highlighting the need to integrate modern amenities with authentic style. The study contributes theoretically by showing how specific architectural features trigger emotions and promote sustainable behaviors, and methodologically by demonstrating the value of qualitative approaches in capturing tourists’ nuanced motivations, perceptions, and experiences. These insights offer practical guidance for guesthouse managers seeking to combine heritage preservation, tourist satisfaction, and sustainable tourism practices. Keywords: guesthouses; Authenticity; traditional architecture; tourist experience; sustainable engagement; sustainable practices; Place attachment; Memorable experience.